Production of Interferon in Mice: Effect of Altered Gaseous Environments - Huang, Kun-Yen (1968)
Effects of altered gaseous environments (parabarosis) on interferon production in mice were studied, with Newcastle disease virus (NDV) as the inducer. Increased levels of interferon in lung tissue were observed when mice were exposed to 11% O(2) in N(2) for 3 days before and after, or only after, injection of NDV. However, serum interferon levels remained unchanged. Exposure of mice to 77% O(2) for up to 7 days did not affect the response to interferon induction as assayed in lungs or sera. Interferon levels were significantly depressed in mice exposed to a simulated depth of 213 ft in seawater [with normal partial pressure of O(2) (pO(2)) in N(2)] for 2 or 4 weeks. Whereas definite depression of interferon was also observed in mice maintained at a simulated altitude of 37,000 ft (with normal pO(2)) for 2 weeks, those maintained at the same condition for 4 weeks showed a normal level of interferon. The results obtained with hypoxia are compatible with other reports on the influence of O(2) tension on viral infection. The factors responsible for alterations observed in interferon level in mice kept in normal pO(2), but under altered pressure, have not yet been identified.